Drivers of Spain's Export Performance and the Role of the Labor Market Reforms - Salas, Jorge (IMF Working Papers; Working Paper ;, 2018)
Spain's export performance strengthened after the global financial crisis, and exports now represent more than a third of GDP. This paper argues that several factors contributed to that achievement: external demand, supported by greater diversification of destination markets; enhanced export orientation of Spanish firms, partly as a response to lower domestic demand after the crisis; and competitiveness gains, reflecting in part changes in the labor market following structural reforms adopted in 2010 and 2012. Based on cross-country panel regressions linking real export growth to employment protection indicators, those labor market reforms are estimated to account for nearly one-tenth to above one-quarter of Spain's total export growth rate from 2010 to 2013.